KEPUASAN KERJA PEGAWAI DINAS PERPUSTAKAAN KABUPATEN NIAS SELATAN - Duha, Timotius; Dakhi, Yohanes (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
Purpose: The aim of this study is to determine the effect of Discipline and Work Environment on Job Satisfaction at the South Nias Regency Library Service, Methods: The number of respondents was 35 employees. Primary data types and research data collection techniques use questionnaire methods Analysis data: The number of respondents was 35 employees. Analysis Tool with multiple linear regression. Primary data types and research data collection techniques used the questionnaire method, while data processing used IBM SPPS Statistics 23 software Result and discussions: The results of the study show that partially Discipline and Work Environment have a positive effect and significant to Job Satisfaction partially and simultaneously.